2022
DOI: 10.1111/iwj.13801
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of chitosan‐based hydrocolloid dressing in the treatment of chronic refractory wounds

Abstract: This retrospective study aimed to explore the clinical efficacy of chitosan‐based hydrocolloid dressing in treating chronic refractory wounds. A total of 80 patients with chronic refractory wounds were randomly divided into the control group (n = 40) and the study group (n = 40). The control group was given inert saline gauze, while the study group was given chitosan‐based hydrocolloid dressing. After 3 weeks of treatment, the wound healing efficiency, itching pain score, changes in the wound area, dressing ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Our extensive literature search, which initially included 1135 articles, culminated in the careful selection of 8 studies 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 for this meta‐analysis. Table 1 provides a detailed overview of these studies, highlighting their key characteristics and methodologies, with a particular focus on the use of hydrocolloid dressings in the context of NIV and maxillofacial surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Our extensive literature search, which initially included 1135 articles, culminated in the careful selection of 8 studies 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 for this meta‐analysis. Table 1 provides a detailed overview of these studies, highlighting their key characteristics and methodologies, with a particular focus on the use of hydrocolloid dressings in the context of NIV and maxillofacial surgery.…”
Section: Resultsmentioning
confidence: 99%
“…23,24 Another report mentioned the use of ultrasound jelly to seal the wound when applying NPWT to the foot, 25 but this was not appropriate in these moisture-prone areas in this study. Hydrocolloid dressings have been widely used in a variety of acute and chronic wounds, such as pressure injuries and post-operative incisions, [26][27][28] and have also shown good results in the treatment of severe diaper dermatitis, 29 demonstrating their moisture-defying, tightly adherent, skin friendly, and comfortable properties. The combined application of hydrocolloid dressings and NPWT was described and analysed in detail for the first time in this study, extending the range of applications for hydrocolloid dressings.…”
Section: Discussionmentioning
confidence: 99%
“… 55 A retrospective study showed a significant improvement in wound healing, degree of pain, and wound itchiness in 80 patients with chronic refractory wounds treated with CS‐based hydrocolloid dressing for 3 weeks. 56 CS shortens the inflammatory phase by facilitating the migration of macrophages and other active cells to clear the inflammatory mediators and cellular debris at the wound site, improving wound healing. 57 CS‐based oligosaccharides significantly reduce lipopolysaccharide‐induced release of proinflammatory cytokines such as IL‐1β, IL‐6, and TNF‐α from the THP‐1 monocytes, indicating the anti‐inflammatory potential of CS.…”
Section: The Need To Incorporate Other Polymers Into the Honey Hydrogelmentioning
confidence: 99%
“…CS's hemostatic nature was demonstrated by the shortened hemostasis time in rat models compared to conventional gauze dressing 55 . A retrospective study showed a significant improvement in wound healing, degree of pain, and wound itchiness in 80 patients with chronic refractory wounds treated with CS‐based hydrocolloid dressing for 3 weeks 56 . CS shortens the inflammatory phase by facilitating the migration of macrophages and other active cells to clear the inflammatory mediators and cellular debris at the wound site, improving wound healing 57 .…”
Section: The Need To Incorporate Other Polymers Into the Honey Hydrogelmentioning
confidence: 99%